Antibacterial Activity And Preliminary Phytochemical Screening Of Epiphytic Moss Stereophyllum Ligulatum Jaeg. - B. L. CHAUDHARY,; PREM KUMAR, (International Journal of Pharma and Bio Sciences, 2011)
Epiphytic moss Stereophyllum ligulatum was collected from Maharastra. The plants were extracted in methanol, ethanol, petroleum ether, acetone and benzene. All the crude extracts tested for antibacterial activity against some pathogenic bacteria viz. Bacillus cereus, Staphylococcus aureus, Escherichia coli, Enterobacter aerogenes and Klebsiella pneumoniae by agar well diffusion method. The plant extracts showed remarkable inhibitory activity on the growth of microorganisms. Phytochemical screening was carried out using standard procedure to identify the constituents as described by Sofowora et al. (1998).